Performance and Capabilities of Small Qualification Contractors on the Sustainable Construction Regulations Implementation - Mochamad Choir; Nusa Sebayang; Maranatha Wijayaningtyas; Wiwik Wiharti (EPI International Journal of Engineering, 2024)
The construction sector is important in Indonesia's economic and social development. With the increasing awareness of the importance of sustainability, implementing sustainable construction principles has become necessary. On the other hand, construction service businesses with small qualifications face various challenges in meeting strict regulations and adapting to sustainable practices. This study aims to analyse the performance and capabilities of sustainable construction services businesses in small qualification contractors in East Java on implementing sustainable construction services business regulations. The research method used is mixed methods, as well as qualitative and quantitative methods. As many as 100 respondents are members of the Gapeksindo East Java association with small qualifications. The results showed that construction service businesses with good management (high managerial ability) tend to be more able to comply with sustainable construction regulations. In addition, the descriptive analysis results show recommendations and strategies to improve the implementation of construction services regulations among small businesses, such as training and education, financial support, Simplification of Regulations, technology and innovation, Increased Market Awareness, and technical assistance. With these strategies, it is expected that small construction service businesses in East Java can be more effective in implementing sustainable construction regulations to improve their performance and contribution to sustainable development.